Ginsenoside Rd inhibits migration and invasion of tongue cancer cells through H19/miR-675-5p/CDH1 axis (Journal of Applied Oral Science, 2022)
Objective: Tongue squamous cell carcinoma (TSCC) is an oral cancer, with high malignancy and frequent early migration and invasion. Only a few drugs can treat tongue cancer. Ginsenoside Rd is a ginseng extract with anti-cancer effects. Many noncoding RNAs are abnormally expressed in tongue cancer, thus influencing its occurrence and development. H19 and miR-675-5p can promote cancer cell growth. This study aimed to analyze the regulation effect of ginsenoside Rd on H19 and miR-675-5p in tongue cancer. Methodology: We used CCK8 and flow cytometry to study the growth and apoptosis. Transwell assay was used to assess invasion; wound-healing assay to assess migration; and colony formation assays to test the ability of cells to form colonies. H19, miR-675-5p, and CDH1 expressions were analyzed by qPCR. E-cadherin expression was detected using western blot. CRISPR/cas9 system was used for CDH1 knockout. Results: Ginsenoside Rd inhibited the growth and increased the apoptosis of SCC9 cells. Ginsenoside Rd also inhibited the migration and invasion of SCC9 cells. H19 and miR-675-5p were highly expressed, while CDH1 and E-cadherin expressions were low. H19 and miR-675-5p promoted SCC9 metastasis. In contrast, CDH1 and E-cadherin inhibited the metastasis of SCC9 cells. Bioinformatics analysis showed that miR-675-5p was associated with CDH1. H19 and miR-675-5p expressions decreased after ginsenoside Rd treatment, while CDH1 and E-cadherin expressions increased. Conclusions: Ginsenoside Rd inhibits tongue cancer cell migration and invasion via the H19/miR-675-5p/CDH1 axis.